2022
DOI: 10.3390/pharmaceutics15010068
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress and Outlook of Nano-Based Hydrogel Dressings for Wound Healing

Abstract: Wound dressing is an important tool for wound management. Designing wound dressings by combining various novel materials and drugs to optimize the peri-wound environment and promote wound healing is a novel concept. Hydrogels feature good ductility, high water content, and favorable oxygen transport, which makes them become some of the most promising materials for wound dressings. In addition, nanomaterials exhibit superior biodegradability, biocompatibility, and colloidal stability in wound healing and can pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 142 publications
0
17
0
Order By: Relevance
“…Fiber dressings such as alginate fiber dressings also have excellent absorbency and are able to fully absorb the wound exudation, keeping the wound relatively dry ( Zhang and Zhao, 2020 ). Since wound healing is affected by many internal and external factors, it has become a new direction for the construction of wound dressings to modify or add a variety of bioactive substances to the existing matrix materials and make them have anti-inflammatory, antibacterial, promoting re-epithelialization and other biological functions ( Zhao et al, 2017 ; Zhang et al, 2022a ; Yao et al, 2023 ).…”
Section: Characteristics Of Wound Dressing In Skin Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiber dressings such as alginate fiber dressings also have excellent absorbency and are able to fully absorb the wound exudation, keeping the wound relatively dry ( Zhang and Zhao, 2020 ). Since wound healing is affected by many internal and external factors, it has become a new direction for the construction of wound dressings to modify or add a variety of bioactive substances to the existing matrix materials and make them have anti-inflammatory, antibacterial, promoting re-epithelialization and other biological functions ( Zhao et al, 2017 ; Zhang et al, 2022a ; Yao et al, 2023 ).…”
Section: Characteristics Of Wound Dressing In Skin Wound Healingmentioning
confidence: 99%
“…An ideal wound dressing should be able to meet the needs of all aspects of the wound healing process and provide the most suitable internal and external environment for cell and tissue regeneration. Firstly, the dressing must have good biocompatibility in the selection of raw materials, and will not cause immune rejection or biological toxicity ( Zhang et al, 2022a ); At the same time, it should have relatively low economic cost, which is convenient for large-scale production and clinical application ( Pagnamenta, 2017 ). The wound dressing constructed should be able to simulate the tissue structure of the skin, have appropriate mechanical strength, and be able to fit closely with the skin without adhesion to the wound, so as to avoid the occurrence of secondary damage ( Alizadehgiashi et al, 2021 ).…”
Section: Characteristics Of Wound Dressing In Skin Wound Healingmentioning
confidence: 99%
“…Overall, the drug-controlled release improves safety by allowing the maintenance of the concentration within the therapeutic window, which can also be enhanced by coating the surface of nanoparticles as a vectorization strategy to achieve target-specific therapies [ 51 ]. Lastly, improved mechanical properties and adhesion of formulations are achieved by preparing nano-based hydrogels [ 25 ].…”
Section: Soft Nanoparticles and Hydrogels For Wound Healingmentioning
confidence: 99%
“…Numerous studies have shown that the association of nanotechnology and wound dressing devices is a promising strategy, especially when nanostructured systems are used to improve the performance of active compounds throughout the skin [ 24 ]. Furthermore, nano-based formulations present improved bioadhesion, physicochemical stability, and biocompatibility [ 25 ], and have sparked scientific and pharmaceutical interest in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels can be classified based on different parameters, including the source of materials (natural or synthetic), polymeric composition (homopolymeric, copolymeric, or multipolymeric), crosslinking mechanism (physical or chemical), sample size (nanogels, microgels, macrogels, or bulk hydrogels), and degradability (degradable or nondegradable) [ 47 , 48 , 49 , 50 ]. Considering the numerous excellent review articles on the introduction, classification, preparation, and application of hydrogels that have already been published [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], we will refrain from providing an exhaustive classification of hydrogels in this work.…”
Section: Hydrogelsmentioning
confidence: 99%